Optimalisasi Media Sosial sebagai Strategi Imarah dalam Pemakmuran Masjid Hizbullah Kudus - Rizqiyah, Siti Fadhilatul; Rochanah, Rochanah (Islamic Management and Empowerment Journal, 2026)
In the digital era, social media has become an effective tool for religious institutions to disseminate information, expand the reach of da’wah, and enhance community engagement. Hizbullah Mosque is one of the mosques that actively utilizes social media for these purposes. This study aims to analyze the social media utilization strategies implemented by Hizbullah Mosque in Kudus and their impact on the implementation of the imarah function in mosque prosperity. This research employed a qualitative approach with a descriptive method through observation, interviews, and documentation. The findings reveal that the use of social media, particularly Instagram, has increased congregational engagement, expanded the reach of da’wah, strengthened the mosque’s positive image, and encouraged greater donor support for various religious and social programs. These findings indicate that social media serves not only as a medium for information dissemination and da’wah but also as an effective strategy for supporting mosque prosperity in the digital era.